Precise variant interpretation, phenotype ascertainment, and genotype-phenotype correlation of children in the EARLY PRO-TECT Alport trial - Böckhaus, Jan Simon; Höfele, Julia; Riedhammer, Korbinian M.; Tönshoff, Burkhard; Ehren, Rasmus; Pape, Lars; Latta, Kay; Fehrenbach, Henry; Lange-Sperandio, Bärbel; Kettwig, Matthias; Hoyer, Peter; Staude, Hagen; et al. (Clinical genetics, 2021)
Early initiation of therapy in patients with Alport syndrome (AS) slows down renal failure by many years. Genotype-phenotype correlations propose that the location and character of the individual's variant correlate with the renal outcome and any extra renal manifestations. In-depth clinical and genetic data of 60/62 children who participated in the EARLY PRO-TECT Alport trial were analyzed. Genetic variants were interpreted according to current guidelines and criteria. Genetically solved patients with X-linked inheritance were then classified according to the severity of their COL4A5 variant into less-severe, intermediate, and severe groups and disease progress was compared. Almost 90% of patients were found to carry (likely) pathogenic variants and classified as genetically solved cases. Patients in the less-severe group demonstrated a borderline significant difference in disease progress compared to those in the severe group (p = 0.05). While having only limited power according to its sample size, an obvious strength is the precise clinical and genetic data of this well ascertained cohort. As in published data differences in clinical progress were shown between patients with COL4A5 less-severe and severe variants. Therefore, clinical and segregational data are important for variant (re)classification. Genetic testing should be mandatory allowing early diagnosis and therapy of AS.